Fear and the Fama-French factors - Durand, Robert; Lim, D.; Zumwalt, J. (Wiley-Blackwell Publishing, Inc., 2011)
Investors’ expectations of market volatility, captured by the VIX (the Chicago Board Options Exchange’s volatility index, also known as the “investor fear gauge”), affects the expected returns of US equities. Changes in the VIX drive variations in the expected returns of the factors included in the Fama and French three-factor model augmented with a momentum factor. The market risk premium (Rm – Rf ) and the value premium (HML) are especially sensitive to changes in the VIX. An increase in expected volatility is associated with flights to quality and increases in estimated required returns.